Effects of pH Value of the Electrolyte and Glycine Additive on Formation and Properties of Electrodeposited Zn-Fe Coatings - İsmail Hakki Karahan (The Scientific World Journal)
Environmentally friendly and cyanide-free sulfate bath under continuous current and the corrosion behavior of electrodeposits of zinc-iron alloys were studied by means of electrochemical tests in a solution of 3.5% NaCl in presence and absence of glycine. The effects of pH on the quality of Zn-Fe coatings were investigated in order to improve uniformity and corrosion protection performance of the coating films. The deposit morphology was analyzed using scanning electron microscopy (SEM), and X-ray diffraction (XRD) was used to determine the preferred crystallographic orientations of the deposits. It was found that the uniformity and corrosion resistance of Zn-Fe coating films were strongly associated with pH of the coating electrolyte. To obtain the effect of pH on the film quality and corrosion performances of the films, the corrosion test was performed with potentiodynamic anodic polarization method. It was also observed that uniformity and corrosion resistivity of the coating films were decreased towards and then improved with increasing pH value of the electrolyte. The presence of glycine in the plating bath decreases the corrosion resistance of Zn-Fe coatings.